609 LUPUS IN SHEEP'S CLOTHING: A CARDIAC TAMPONADE DUE TO ACUTE POLYSIEROSITIS IN A SLE PATIENT. (15th December 2022) - Alberti, Giorgia; Dotto, Alberto; Roccabruna, Alessandra; Zagarese, Giorgia; Piccolo, Solange; Cubich, Mattia; Prati, Daniele; Pazzi, Sara; Gambaro, Alessia; Butturini, Caterina; Scarsini, Roberto; Ferrero, Valeria; et al.
Abstract: This case describes a cardiac tamponade in systemic lupus erythematosus (SLE), an uncommon but life-threatening condition that needs prompt recognition. A 33-year-old woman with therapy-resistant SLE presented to the Emergency Department with chest pain and fever for 3 days. She was hemodynamically stable, the ECG showed signs of pericarditis and echocardiography showed a minimal pericardial effusion. Pericarditis was diagnosed and the patient was admitted to the Cardiology Ward. Seven hours later her symptoms deteriorated, presenting hemodynamic instability with hypotension and tachycardia. The ECG showed low QRS voltage and electrical alternans, echocardiography confirmed cardiac tamponade. The patient underwent an emergency pericardiocentesis with 220 mL of serous citrine liquid removed and immediate regression of symptoms. The cytology exam revealed inflammatory cells with no evidence of malignancy, blood culture and effusion fluid's tests came back negative. A Thoraco-abdominal CT revealed also bilateral pleural effusion (not present at the admission) and ascites. Signs, symptoms and medical history suggested SLE flare-up and high-dose oral glucocorticoid therapy was started. Our report highlights a rare presentation of life-threatening polyserositis in SLE flare-up. Although pericarditis and pericardial effusion are frequently-reported SLE's cardiovascular complications, rapid development of cardiac tamponade is far from common. Acute cardiac tamponade, like in our case, is an indication for emergency pericardial drainage to restore an adequate cardiac output. We describe an out of ordinary case of a patient in whom an accurate and timely diagnosis of SLE–related cardiac tamponade has been live–saving.